Challenges and strategies in the prevention and management of surgical site infections in general surgery: a comprehensive review - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
The present study addresses strategies for the prevention and management of surgical site infections (SSI) in general surgery. The importance of preoperative antibiotic prophylaxis, the preparation of the patient’s skin, and the meticulous surgical technique in reducing the incidence of SSI are highlighted. During surgery, maintaining a sterile environment and minimizing tissue manipulation are crucial. After surgery, post-operative care, such as wound monitoring and patient education, is essential. SSIs negatively impact patient recovery and increase hospital costs. Implementing evidence-based practices is critical to improving patient safety and reducing costs associated with SSIs.